2011
DOI: 10.3856/vol39-issue2-fulltext-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of the microalgae Chaetoceros calcitrans (Paulsen): analysis of the effect of DMSO temperature and light regime during different equilibrium periods

Abstract: ABSTRACT.We evaluated the effect of three variables (cryoprotectant temperature, light regime, and time of exposure to the cryoprotectant) throughout the equilibrium period during cryopreservation on the viability of the microalga Chaetoceros calcitrans (Paulsen). For this, the cryoprotectant dimethyl sulfoxide (DMSO) at 5% (v/v) was added at three different temperatures (4, 10, and 25ºC) before placing the microalgae in cryobiological straws for freezing. Once inside the cryobiological straws, the microalgal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(70 reference statements)
0
6
0
1
Order By: Relevance
“…With the exception of C. calcitrans (Salas‐Leiva, ), we did not found specific protocols designed for the cryopreservation of the microalgae that we use for O. dioica feeding, and therefore, we modified the conditions of some general protocols that used dimethyl sulfoxide (DMSO) as cryoprotectant (Day, ). To cryopreserve our microalgae, 1 mL of densely growth culture (i.e., OD > 0.25 for Isochrysis sp .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…With the exception of C. calcitrans (Salas‐Leiva, ), we did not found specific protocols designed for the cryopreservation of the microalgae that we use for O. dioica feeding, and therefore, we modified the conditions of some general protocols that used dimethyl sulfoxide (DMSO) as cryoprotectant (Day, ). To cryopreserve our microalgae, 1 mL of densely growth culture (i.e., OD > 0.25 for Isochrysis sp .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The most important factors, which effects on algal viability, are the type, concentration and timing of cryoprotective agents, pretreatment with cryoprotectant and duration of cryopreservation [11]. Salas-Leiva and Dupré [12] reported that concentration, temperature and time of exposure are related to the use of cryoprotectant in additionally there are various methods of handling them emphasized in the literature. The cryoprotectant agent as DMSO is used for the treatment of microalgae because it easily permeates cell membranes and its low hydrophilicity [13].…”
Section: Resultsmentioning
confidence: 99%
“…Batch cultures of C. calcitrans using micro-filtered sterile sea water were grown. Culture conditions, cryopreservation protocol and viability estimations are broadly described in Salas-Leiva and Dupré (2). A brief description of the cryopreservartion protocol is presented here: dimethylsulfoxide (Me2SO, 10%) (Sigma, St. Louis, MO) was added to the cells at 4 and 25°C in complete darkness (1:1 proportion in mL).…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, cuando la viabilidad posterior a la criopreservación es baja, como lo es en el caso de Chaetoceros calcitrans (viabilidad <40%) (2), es necesario indagar si los microorganismos sobrevivientes presentan una composición proximal similar a la observada en la cepa antes de ser criopreservada, es decir, si la cepa conserva las características nutricionales iniciales. Resultados obtenidos por Sánchez-Saavedra y Nuñez-Zarco (3) indican que el almacenamiento a baja temperatura de refrigeración (4°C) (durante 1 a 6 semanas) influye en la densidad celular y en la composición proximal de los cultivos de las diatomeas Navicula sp, N. incerta, N. thermalis y Nitzschia laevis.…”
Section: Introductionunclassified